2017
DOI: 10.1038/bjc.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the presence of colon cancer in members of a health maintenance organisation by evaluating analytes from standard laboratory records

Abstract: Background:A valid risk prediction model for colorectal cancer (CRC) could be used to identify individuals in the population who would most benefit from CRC screening. We evaluated the potential for information derived from a panel of blood tests to predict a diagnosis of CRC from 1 month to 3 years in the future.Methods:We abstracted information on 1755 CRC cases and 54 730 matched cancer-free controls who had one or more blood tests recorded in the electronic records of Maccabi Health Services (MHS) during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Tables S11-S17 shows the results from analyses of these five components for colorectal cancer diagnosis. Goshen 2017 [28] report a statistically significant difference in mean levels of each of these components between those with and without a diagnosis within 6 months for males and females (t-test all p < 0.05), except lymphocytes for males (t-test p = 0.43). Huang 2019 [36] showed no difference in mean lymphocyte levels between cases and controls (p ≥ 0.05) or those with benign polyps (p ≥ 0.05) zero to six months before diagnosis.…”
Section: Differential White Blood Cell Countmentioning
confidence: 95%
See 1 more Smart Citation
“…Tables S11-S17 shows the results from analyses of these five components for colorectal cancer diagnosis. Goshen 2017 [28] report a statistically significant difference in mean levels of each of these components between those with and without a diagnosis within 6 months for males and females (t-test all p < 0.05), except lymphocytes for males (t-test p = 0.43). Huang 2019 [36] showed no difference in mean lymphocyte levels between cases and controls (p ≥ 0.05) or those with benign polyps (p ≥ 0.05) zero to six months before diagnosis.…”
Section: Differential White Blood Cell Countmentioning
confidence: 95%
“…Panagiotopoulou 2014 [49] suggest that the odds of diagnosis in three months do not differ between those with mean corpuscular volume < 80 fL and ≥ 80 fL when unadjusted (OR = 1.73, 95% CI = 0.96-3.1), but do when adjusted for other factors (OR = 2.2, 95% CI = 1.2-4.1). Goshen 2017 [28] reported a statistically significant difference in mean corpuscular volume between those with and without a future diagnosis (t-tests p < 0.0001), with cases having 3.67 fL lower on average. Ay 2015 [15] reported that, on average, mean corpuscular volume did not statistically significantly differ between those with a diagnosis and those with a benign colorectal polyp (t-test p ≥ 0.05).…”
Section: Mean Corpuscular Volumementioning
confidence: 97%
“…It is possible that the performance of future versions of ColonFlag could be improved using a broader array of standard laboratory tests[ 8 ] or by increasing the number of risk factors included in the algorithm. For example, smoking, body mass index and family history of colorectal cancer are commonly recorded in a patient’s electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
“…We have described the development and validation of the ColonFlag score (previously known as MeScore), an algorithm that incorporates patient factors (age and gender) with complete blood count information (CBC) and which is used to predict the presence of colorectal cancer at the time of testing. [ 6 8 ] ColonFlag was developed using data from healthy Israelis (Maccabi Health Care Services, MHS) and colorectal cancer patients. Training of the model was done using the MHS database and the Israeli National Cancer Registry, which documents invasive colorectal cancer but does not document pre-cancerous lesions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, anaemia in FBC data from UK primary care predicts the risk of colorectal cancer and iron deficiency is an independent risk factor 8. In the last few years, a number of individual studies have reported on the association between the components of the FBC, including haemoglobin, platelet count and red cell distribution width, and diagnosis of colorectal cancer 9–13. Furthermore, risk scores have recently been developed using methods that incorporate FBC data as predictors of colorectal cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%